Princeton Memorandum on the Future of Multilateralism: 14 Points on Principles and Current Contexts - Stefan Kolev; Harold James (Ludwig-Erhard-Forum für Wirtschaft und Gesellschaft (LEF), 2026)
Multilateralism will outlive the current crisis and contestation. We live in a world which is as interdependent on multiple levels of integration as never before - undoing or radically regrouping these interdependencies would be much more difficult, and much more costly, than many of today's enemies of multilateralism believe. The past weeks have shown that, due to this profound integration, a country like Denmark is not powerless and not at the mercy of the new great power politics. Today, multilateralism for many is a deeply problematical concept, reeking of globalism and world government. In China and the "Global South" the postwar multilateral order has long been distrusted as a euphemism for the difficulties of throwing off painful legacies of impe rial rule. But at the same time, we are very worried by unilateralism, and do not want to see a world dominated by a capricious unipolar superpower, whether an increasingly erratic United States or a rapidly growing communist and autocratic China super-charged by AI. Looking for a genuine multilateralism, in which countries of different sizes and histories can work out cooperative solutions to common challenges and problems, becomes thus ever more urgent. This Princeton Memorandum is based on the reflections at the conference The Geoeconomic Resilience of Multilateralism: Power for Some or Prosperity for All?, organized by the Ludwig Erhard Forum for Economy and Society in cooperation with Princeton's Program in Contemporary European Politics and Society and the Bendheim Center for Finance. The conference took place in October 2025 at Princeton University. Our memorandum consists of 14 points. We first revisit seven principles of multilateralism as pillars of this order of the global economy, especially after the Second World War. Subsequently we develop seven arguments to underline our optimism and vision why multilateralism - most probably in a renewed form amid the new friends-foes-constellation we depict - is still likely to shape the decades to come.
Keywords: 330